ÐŸÐ¾Ð³Ñ€ÐµÑˆÐ½Ð¾ÑÑ‚Ð¸ Ð¿Ñ€Ð¸ Ð¾Ð¿Ñ€ÐµÐ´ÐµÐ»ÐµÐ½Ð¸Ð¸ Ð¾Ñ‚Ð½Ð¾ÑÐ¸Ñ‚ÐµÐ»ÑŒÐ½Ð¾Ð³Ð¾ ÐºÐ¾Ð»Ð¸Ñ‡ÐµÑÑ‚Ð²Ð° Ð½ÐµÐ³ÐµÐ¼Ð¾Ð»Ð¸Ð·Ð¸Ñ€Ð¾Ð²Ð°Ð²ÑˆÐ¸Ñ… ÑÑ€Ð¸Ñ‚Ñ€Ð¾Ñ†Ð¸Ñ‚Ð¾Ð² Ð² ÐºÑ€Ð¸Ð¾Ð±Ð¸Ð¾Ð»Ð¾Ð³Ð¸Ñ‡ÐµÑÐºÐ¸Ñ… ÑÐºÑÐ¿ÐµÑ€Ð¸Ð¼ÐµÐ½Ñ‚Ð°Ñ… - Zinchenko, V. D.; Buryak, I. A.; Volovelskaya, E. L. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2007)
Experimental requirements, during meeting of which the value of confidence interval for the integrity of cryopreserved erythrocytes of a donor makes 1.5–6.0% with 0.95 confidence probability, have been established.